2006
DOI: 10.1108/02621710610684259
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between personality and transformational leadership

Abstract: The relationship between personality and transformational leadership Tiina M. Hautala Article information:To cite this document: Tiina M. Hautala, (2006),"The relationship between personality and transformational leadership", Journal of Management Development, Vol. 25 Iss 8 pp. 777 -794 Permanent link to this document: http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 44 publications
5
39
1
1
Order By: Relevance
“…This Extraversion, openness and conscientiousness argument is explained, quite succinctly, by Schyns and Sanders (2007), who identify a number of mediating factors in leadership research, including mood, and personality of followers. Furthermore, in her study of the relationship between personality and transformational leadership, Hautala (2006) found that the ratings of leaders and followers, regarding leaders' transformational leadership behaviour, were not congruent when the focus was on the leader's personality. For future studies of this type, we would suggest that the views of followers, in the Cypriot hotel sector, were also included because the perceptions of leadership styles are likely to vary between those who lead and those being led (Moss and Ngu, 2006).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This Extraversion, openness and conscientiousness argument is explained, quite succinctly, by Schyns and Sanders (2007), who identify a number of mediating factors in leadership research, including mood, and personality of followers. Furthermore, in her study of the relationship between personality and transformational leadership, Hautala (2006) found that the ratings of leaders and followers, regarding leaders' transformational leadership behaviour, were not congruent when the focus was on the leader's personality. For future studies of this type, we would suggest that the views of followers, in the Cypriot hotel sector, were also included because the perceptions of leadership styles are likely to vary between those who lead and those being led (Moss and Ngu, 2006).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…In an effort to identify and therefore predict effective leadership behaviour, research has focused on the relationship between personality and leadership traits (Hautala, 2006).…”
Section: Extraversion Openness and Conscientiousnessmentioning
confidence: 99%
“…Additional research by Hautala (2006) found a relationship between personality as measured by the MBTI and transformational leadership as measured by the Leadership Practices Inventory. Extraversion, intuition, and perceiving were positively associated with transformational leadership.…”
Section: Leadership and Personalitymentioning
confidence: 96%
“…Some of these are the five-factor model or "big five" (DeYoung and others 2007), NEO Personality Inventory (Myers, McCaulley, Quenk and Kammer 1998). Owing to its usefulness and comprehensible approach it has become a common method when studying organisations (Hautala 2006). Like any dominant paradigm, the MBTI ® has drawn its fair share of criticisms and proposals for alternatives.…”
Section: Different Cognitive Styles Between Individualsmentioning
confidence: 99%